A snapshot view of some vertical distributions of water parameters at a deep (200 m) station in the fjord-like Golfo Dulce, embayment, Costa Rica - Acuña-González, Jenaro A. (2006)
Temperature, salinity, dissolved oxygen and inorganic nutrients were measured at a single station in the water column (200 m) of Golfo Dulce, a fjord-like embayment on the Pacific coast of Costa Rica, from June 1993 to September 1995. Eight sampling field trips were carried out and water samples were collected with 5 L Niskin bottles at 10 m depth intervals. Temperature vertical profiles revealed a thermocline between 25 and 60 m. Salinity profiles evidenced a surface layer containing a halocline around 40 m, overlaying a thick 34 ‰ layer on top of a large bottom layer of 35 ‰. Surface-oxygen saturation percentages were usually high, but from 60 m depth down to the bottom (200 m), dissolved oxygen concentrations were low during the whole study, ranging from 3.00 mg/L to 0.20 mg/L, although anoxic conditions were not detected. Bottom waters were rich in inorganic phosphate, silicate, and nitrate, suggesting that its main source is the sporadic influx of ocean water mass entering the gulf at the sill depth (60 m). The pattern of the vertical nitrite concentration suggested that the anammox process can result as a consequence of bacteria existing at low oxygen concentrations at depth. These observations are in agreement with those reported in other surveys since 1971. Rev. Biol. Trop. 54 (Suppl. 1): 193-200. Epub 2006 Sept. 30.